2018
DOI: 10.1002/hyp.11418
|View full text |Cite
|
Sign up to set email alerts
|

Mediating stream baseflow response to climate change: The role of basin storage

Abstract: Inter‐basin differences in streamflow response to changes in regional hydroclimatology may reflect variations in storage characteristics that control the retention and release of water inputs. These aspects of storage could mediate a basin's sensitivity to climate change. The hypothesis that temporal trends in stream baseflow exhibit a more muted reaction to changes in precipitation and evapotranspiration for basins with greater storage was tested on the Oak Ridges Moraine (ORM) in Southern Ontario, Canada. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…BFI values were within the range reported for longer streamflow records from 60 basins draining the ORM (Buttle et al, ), and for basins across south central Ontario which included the ORM region (McLean & Watt, ). FDC slopes were similar to values from Buttle () for the 2006–2012 period for several of the basins examined here. Conversely, Burn et al () gave a mean ( Q 5 – Q 95 )/ Q 50 of 7.7 for basins in southern Ontario that exceeds values for most of the study basins (Table ); our lower values likely reflect the role of storage in the ORMAC in mediating translation of inputs to streamflow and producing more stable flow regimes.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…BFI values were within the range reported for longer streamflow records from 60 basins draining the ORM (Buttle et al, ), and for basins across south central Ontario which included the ORM region (McLean & Watt, ). FDC slopes were similar to values from Buttle () for the 2006–2012 period for several of the basins examined here. Conversely, Burn et al () gave a mean ( Q 5 – Q 95 )/ Q 50 of 7.7 for basins in southern Ontario that exceeds values for most of the study basins (Table ); our lower values likely reflect the role of storage in the ORMAC in mediating translation of inputs to streamflow and producing more stable flow regimes.…”
Section: Discussionsupporting
confidence: 82%
“…They should also consider the potential scale‐dependence of the influence of such factors as hydrogeologic conditions on the storage indices examined here. Gerber and Howard () and Buttle () noted that lower stream reaches in several basins (e.g. Pefferlaw Br) are incised into deeper aquifers confined by the Newmarket Till.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was an upward trend with the annual baseflow index in the upstream and no statistically significant difference in middle and downstream in the Loess Plateau in China [24]. Buttle [25] presented that baseflow discharge had an increasing trend and a decreasing trend with total precipitation in Oak Ridges Moraine in Canada. Kahsay et al [26] reported that baseflow decreased in the sub-catchment of the Tekeze basin in Ethiopia from 1994 to 2013.…”
Section: Introductionmentioning
confidence: 94%